TI_GERICHTE 12.2017.152 vom 19. Juni 2018 , Azione di inesistenza del debito - contumacia - atto sconveniente e prolisso - TI Tribunale d'appello (2018)
Azione di inesistenza del debito - contumacia - atto sconveniente e prolisso